ANALISA KELAYAKAN USAHA KERIPIK UBI UNGU PADA UKM BIMA SAKTI MAJALAYA BANDUNG - Samsul Arifin (Ma'soem University, 2021)
This study aims to analyze the feasibility of purple potato chips, (The case of the Bima Sakti UKM, Majalaya District, Bandung Regency). Determination of location in this study have choosen purposively, with consideration that in Bima Sakti UKM, Majalaya District, Bandung Regency, Analysis of the data used in this research is the analysis of R / C Ratio and BEP analysis. The results showed that the purple potato chips business in Bima Sakti UKM, Majalaya District, Bandung Regency to be developed either from the analysis of R / C Ratio and of BEP analysis. Based on the analysis of R / C Ratio obtained a value of 1.67 which means that the business is feasible to be developed because the value of R / C ratio is greater than one. BEP Analysis of results showed that the average amount of production per one month is 3.600 kg greater (>) than with the BEP production 17,2 Kg. Similarly, the calculation results BEP receipts (IDR) also shows that business in Bima Sakti UKM purple potato chips feasible to be developed, because the average amount of revenue (IDR) per one month is Rp. 72.000.000 more large (>) compared with BEP receipts (IDR) Rp. 344.000.